Unveiling the Microbial Contribution to Preterm Birth : The Role of Asymptomatic Bacteriuria obial Contribution to Preterm Birth: The Role of Asymptomatic Bacteriuria - Yossra Saleh Khudhur; Huda Saleh Khuder; Shaimaa Saleh Khudhur (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Background: Preterm labor (PTL) remains a major global health concern, contributing significantly to neonatal morbidity and mortality. Asymptomatic bacteriuria (ASB), has been implicated as a predisposing factor to PTL. This research investigates association between ASB and PTL, emphasizing inflammatory mediators such as high-sensitivity C-reactive protein along with tumor necrosis factor- α. Methods: This observational case-control study was conducted at Tikrit Teaching Hospital, Iraq, involving 100 pregnant women (50 PTL cases and 50 full-term controls). Demographic, clinical, and laboratory data were collected. Urine cultures identified bacterial isolates. In addition, levels of TNF-α and hs-CRP in serum were measured using ELISA. Statistical analyses were performed using SPSS.  Results: ASB was significantly associated with PTL, with 30% from PTL cases having a positive urine culture compared to 8% in controls (p = 0.009). Escherichia coli was the predominant pathogen (53%). TNF-α and hs-CRP levels were significantly elevated in PTL cases (p < 0.001), suggesting an inflammatory pathway in PTL pathophysiology. Conclusions: ASB is a significant risk factor for PTL, likely mediated by systemic inflammation. Routine ASB screening and targeted antimicrobial therapy may reduce PTL risk. Further study is required to explore the mechanistic connections amongst microbial infection and inflammatory responses in PTL.